C-reactive protein levels in febrile patients admitted to a tertiary care teaching hospital - Timilsina, Mukunda; Gauchan, Eva (Journal of Chitwan Medical College, 2025)
Introduction: C-reactive protein (CRP) is an acute-phase reactant used as a diagnostic and prognostic marker in infectious and inflammatory conditions. This study evaluated the utility of CRP with symptom severity and hospital stay in febrile patients aged 6-60 months admitted to Manipal Teaching Hospital, Nepal. Method: A cross-sectional study was conducted from 01 Nov 2024 to 30 Apr 2025, involving 194 febrile children admitted to the paediatric department after ethical approval from institutional review committee. Sample size was calculated using correlation coefficient estimation. Inclusion criteria were complete medical records and available CRP data; exclusions were parents who declined consent for their children. The association between CRP levels, symptom severity, and the length of hospital stay. The IBM SPSS was used to analyse data. A p≤0.05 was considered significant. Result: In 194 febrile paediatric patients, the mean age was 30.98 months. Common symptoms were cough 90(46.4%), vomiting 55(28.4%), and seizures 41(21.2%). The CRP levels varied, with higher levels associated with higher grades of fever (p=0.005) and longer hospital stays (r=0.45, p<0.001). Children with CRP levels >48 mg/l had an average hospital stay of 7.8 days, compared to 4.5 days for those with lower CRP levels. Conclusion: Elevated CRP levels may be associated with increased severity and longer hospitalisation. Further research is needed to standardise and use age CRP levels in management of febrile paediatric patients in resource-limited settings like Nepal.